Islam Opportunities in the Era of Globalization (Case Study of Da'wah in Sosial Media): Peluang Islam Terhadap Era Globalisasi (Studi Kasus Dakwah dalam Media Sosial) - Noviana, Hanna; Ramdani, Muhammad; Najmahul Umam, Muhammad Mufti (JSPH : Jurnal Sosial Politik Humaniora, 2025)
This research examines the opportunities for Islam in the era of globalization, a case study of da'wah on social media. This research aims to analyze the opportunities for Islamic da'wah in the era of globalization with a focus on the use of social media as a medium for da'wah. social media itself is an effective means of spreading da'wah messages globally, the results of this research are that the opportunity for Islam in the era of globalization is that social media has a very important role, da'wah messages can be spread quickly and effectively through social media, reaching a wider audience, however, the use of social media in preaching must be wise and responsible. The research method used is a case study, by analyzing preaching content delivered through platforms such as Instagram, YouTube and TikTok. The research results show that social media can be an effective tool in conveying Islamic values creatively, interactively and easily accessible. Apart from that, the use of social media is able to reach the younger generation who make up the largest part of internet users. However, challenges such as hoaxes, disinformation and misinterpretations of Islamic teachings also require special attention. Therefore, an innovative da'wah approach is needed that is appropriate to the digital context to maximize the opportunities offered by the era of globalization.